Encapsulating FeCo alloys by single layer graphene to enhance microwave absorption performance. (December 2021) - Cui, X.J.; Jiang, Q.R.; Wang, C.S.; Wang, S.H.; Jiang, Z.Y.; Li, X.A.; Deng, D.H.
Abstract: Graphene/magnetic metal hybrid nanostructures are promising candidates of novel microwave absorption materials. Although many efforts have been devoted to fabricate various graphene/magnetic metal hybrid composites, the microwave absorption performance of these materials is still far from industrial demand due to the not well balance between electric field and magnetic field characteristics. Herein, we report single layer graphene encapsulating FeCo alloy nanoparticles (FeCo@Cs) with excellent microwave absorption performance, which deliver a reflection loss value exceeding −10 dB in the whole Ku-band, whole X-band, whole C2-band, and even in the whole C1-band by varying the absorber thickness. The control experiments and numerical simulations demonstrate that the introduction of graphene coating on FeCo alloy nanoparticles can improve the microwave absorption performance greatly by increasing the electrical loss. Moreover, decreasing the coating thickness to single layer graphene can render a good match between electric field and magnetic field, and thus resulting in an electrifying microwave absorption performance. This work gives new insights into the absorption enhancement of graphene/magnetic metal hybrid structures and contributes to guide the design and development of highly efficient microwave absorption materials for practical application. Graphical abstract: Image 1 Highlights: ● Single layer graphene encapsulating FeCo alloy nanoparticles (FeCo@Cs) have been successfully fabricated. ● The introduction of graphene coating on FeCo alloy nanoparticles can improve the microwave absorption performance greatly by increasing the electrical loss. ● The effective absorption bandwidth of FeCo@Cs can reach 8.3 GHz with thin thickness.